Digital Marketing Development Strategy for Sharia Consumer Cooperatives with Business Model Canvas - Tati Handayani; Sufyati HS; Prima Dwi Priyatno; Nurhafifah Matondang; Yudi Nur Supriadi (Garuda Prestasi Nusantara Consulting, 2023)
Globalization has brought increasingly fierce competition for Islamic cooperatives, which threatens their survival in the market. As one of the important business sectors, sharia cooperatives need to develop strategies to remain relevant in various services, including financial services. The purpose of this study is to evaluate the business model and provide alternative recommendations for developing digital marketing with a business model canvas approach. This study uses a qualitative method with a business model canvas approach and the selected sharia cooperative model is the Baiturrahman Mitra Umat Sharia Consumer Cooperative (KKS). The results showed that the Baiturrahman Mitra Umat PSC experienced growth. The strategy that needs to be implemented should focus on growth that improves service, profit, and exploring new opportunities by prioritizing the role of digitalization for the marketing process of cooperative services. This strategy is formulated based on nine elements of the business model canvas, including customer segments, value proposition, distribution channels, customer relationships, revenue streams, key resources, key activities, key partnerships, and cost structure. Keywords:business model canvas, digital marketing, sharia cooperative, marketing strategy